Studies on the Pyrolysis of Composite Solid Propellants leading to Ignition - Kishore, K.; Sankaralingam, S. (Defence Science Journal, 2014)
Studies on the pyrolysis leading to ignition of polystyrene (PS)/ammonium perchlorate (AP), polyvinyl chloride (PVC)/AP and polyphenol formaldehyde (PPF)/AP propellants revealed that the activation energy for the ignition strongly depends upon the binder. Double base propellants exhibit an empirical relationship between the ignition delay ( ) and the oxidiser concentration; when the same equation is applied to composite solid propellants, the plot of In vs In C (C=Concentration, %) yields a straight line with a knee corresponding to 65-70 per cent AP above which the dependence on becomes less sensitive.